Immediate or Delayed Breast Reconstruction After Radical Mastectomy in Breast Cancer Patients: Does It Make a Difference in the Quality of Life - GÜLLÜOĞLU, MAHMUT BAHADIR (ORTADOGU AD PRES & PUBL CO, 2011)
Objective: Nowadays, most of the women with breast cancer are diagnosed in early stages and benefit from regional and systemic treatments with proven efficacy. Various methods of breast reconstruction can be applied to patients who undergo mastectomy at different times. The purpose of this study is to investigate how immediate or delayed breast reconstruction affected the patients' quality of life after mastectomy. Material and Methods: Breast cancer patients who had reconstructive surgery at any time after mastectomy were included in the study. Measures for evaluating the patients' psychopathological status (SCL-R90 Symptom checklist) and quality of life (EORTC QLQ-C 30) were used. Demographical and clinical data were obtained retrospectively from the patients and their hospital records. Demographical and clinical data were analyzed retrospectively, quality of life parameters were analyzed as descriptive statistics in a single time period. Patients who had undergo immediate (28 patients) or delayed (23 patients) breast reconstruction after mastectomy in Marmara University Hospital between January 1, 2002 and December 12, 2006 were included in the study. Results: When compared with the delayed reconstruction group, patients in the immediate reconstruction group were found to be at earlier stages and thus, there was less need for radiotherapy. Delayed reconstruction was mainly utilized in patients who received adjuvant therapy and axillary lymph node dissection. There was no difference between the two groups regarding their demographical characteristics. This study revealed that immediate reconstruction, when compared to delayed reconstructive surgery, improved patient's body image, self-esteem, and family/social relations. It also increased the quality of life psychologically, socially and spiritually as well as decreased somatic complaints. Conclusion: Immediate breast reconstruction after mastectomy in compared to delayed one, positively affects the individual's quality of life.
Keywords: Quality of life; breast neoplasms; mammaplasty; RADIATION-THERAPY; SURVIVORS; SURGERY; LYMPHEDEMA; WOMEN; SATISFACTION; RELIABILITY; DISTRESS; VALIDITY